One life [videorecording (DVD)] - Coxon, Lucinda, 1962-; Drake, Nick, 1961-; Hopkins, Anthony, 1937-; Flynn, Johnny; Olin, Lena; Garai, Romola, 1982-; Sharp, Alex, 1989-; Keller, Marthe; Pryce, Jonathan; Bonham Carter, Helena, 1966-; Nicholson, Zac, 1971-; Bertelmann, Volker, 1966-; et al. (Decal Releasing, 2024)
Tells the truet story of Nicholas Winton, who organized the rescue of hundreds of predominantly Jewish children from the Nazis on the verge of World War II. Half a century later, he is haunted by the memory of those he could not save.